Изучение влияния этанола на антигены А, В, Н при установлении групповой принадлежности крови по изосерологической системе АВО как одного из этапов идентификации личности - Ажицкая, Н.Н.; Голубинская, Н.Б.; Тишенко, С.В.; Смуглова, Н.В. (Таврический медико-биологический вестник, 2013)
Показана обернено-пропорційна залежність ступеня вираженості специфічних властивостей антигенів крові за ізосерологічною системою АВО (кількісного показника антигенних детермінант на еритроцитах) від кількості проміле етанолу в крові та запропоновано методи усунення впливу алкоголю на антигенну структуру крові. У ході дослідження використовувалися методики визначення групи крові в рідкому вигляді, реакція абсорбції в кількісній модифікації – КРА, реакція абсорбції-елюції – РАЕ. Inversely proportional dependency of manifestation of the blood antigen specific properties in the ABO system (a quantitative indicator of antigenic determinants on erythrocytes) on the amount of ethanol promille in the blood has been shown and methods to eliminate the alcohol influence on the blood antigenic structure has been suggested. The methods for determining the blood groups in the liquid state, the absorption reaction in the quantitative modification – Quantitative Agglutinin-absorption Test, and the reaction of absorption-elution (AER) were used in the study.